Bipolar vaporization of hemorrhoidal nodes in stage III chronic hemorrhoids: a single-centre comparative study involving laser hemorrhoidoplasty, transanal dearterialization, and Longo surgery - Bilianskyi, L. S.; Voloshyn, I. V. (General Surgery, 2025)
Objective – to compare the effectiveness and safety of bipolar vaporization (BPV) of hemorrhoidal nodes with laser hemorrhoidoplasty (LHP), transanal dearterialization (THD), and stapled hemorrhoidopexy (Longo surgery) in patients diagnosed with stage III chronic hemorrhoids. Materials and methods. A single‑centre, prospective, comparative study was conducted involving 63 patients (35 women and 28 men) with symptomatic stage III chronic hemorrhoids treated between 2021 and 2024. The mean age was 45.3±11.1 years, the mean body mass index was 26.8 kg/m2, and the mean disease duration was 10.3±6.7 years. Patients were allocated to four groups based on the treatment method: BPV (n=18, 28.6%), LHP (n=15, 23.8%), THD (n=16, 25.4%), and Longo surgery (n=14, 22.2%). Bipolar vaporization was performed according to the author’s method using the biowelding generator EK‑300M (Svarmed, Ukraine) with multi‑cycle vaporization of the node. Outcomes assessed included symptoms, complications, recurrences, patient satisfaction, duration of surgery, and length of hospital stay. Results. The mean duration of surgery was 45.2±6.3 minutes in the BPV group, 44.5±7.5 minutes in the LHP group, 43.4±6.2 minutes in the THD group, and 41.1±4.9 minutes in the Longo surgery group (p>0.05). Blood loss ranged from 10.4 to 16.4 ml across all groups (p>0.05). The incidence of submucosal hematomas did not exceed 35% in any group. All techniques resulted in a significant reduction in hemorrhoid symptoms postoperatively (p<0.05 within groups). At one year post‑surgery, recurrence rates were 5.6% for BPV, 6.7% for LHP, 18.8% for THD, and 21.4% for Longo surgery (p=0.422). Patient satisfaction scores at 12 months ranged from 7.7 to 8.1 points. Conclusions. Bipolar vaporization demonstrates effectiveness comparable to other minimally invasive techniques for the treatment of grade III chronic hemorrhoids, with minimal trauma and a short postoperative recovery period. The method is cost‑effective due to the use of reusable electrodes. Bipolar vaporization is recommended for broader adoption in proctological practice, particularly in resource‑limited settings.